Nomogram for stratifying patients with lifelong premature ejaculation before using the PHQ‐9: An observational study. (22nd May 2022) - Hou, Guangdong; Gao, Ming; Zheng, Yu; Hou, Niuniu; Zhang, Siyan; Sun, Jianhua; Jannini, Tommaso B.; Zhang, Lei; Dun, Xinlong; Wang, Fuli; Jannini, Emmanuele A.; Yuan, Jianlin
Abstract: Objective: A PHQ‐9 score ≥ 15, represented as PHQ‐9 +, indicates major depressive disorder (MDD). On using PHQ‐9, the psychological burden of several patients with lifelong premature ejaculation (LPE) gets aggravated, which may lead to LPE development. We aim to construct a nomogram for predicting the individual risk of PHQ‐9 + in patients with LPE and discerning those with low risks, who should avoid the PHQ‐9. Methods: The nomogram was constructed by analysing data of 802 patients from Xijing Hospital and Northwest Women's & Children's Hospital. The LASSO and multivariable logistic regressions were used to identify independent predictors of PHQ‐9 +, used for developing the nomogram. The discrimination, calibration and clinical usefulness of the nomogram were assessed in the derivation cohort and an independent validation cohort, which was composed of 505 prospectively enrolled patients from Daxing Hospital and Xijing Hospital. Results: The duration of PE, IELT, a history of PE exacerbation, IIEF‐5 score, urinary frequency and physical pain score were identified as independent predictors. The nomogram showed excellent calibration, discrimination and clinical usefulness in the derivation and validation cohorts, with a predictive accuracy of 0.781 and 0.763, respectively. Based on this nomogram, patients were divided into not recommended, recommended and strongly recommended PHQ‐9 filling groups, with PHQ‐9 + rates of 3.5%, 9.3% and 30.7%, respectively. Conclusion: A nomogram to discern LPE patients with low risks of PHQ‐9 + was established. This tool can increase the positivity of MDD screening and may improve the therapeutic outcomes of those in the low‐risk group.